Integration of Islamic Values in Guidance and Counseling Services as a Strategy for Strengthening Character Education - Nur Hotimah (Global Education Journal, 2026)
Character education has become a central concern in contemporary educational discourse due to the increasing complexity of moral, social, and psychological challenges faced by students in the modern era. This study aims to analyze the integration of Islamic values ​​in guidance and counseling services as a strategic approach to strengthening character education in educational institutions. A descriptive qualitative research design was used, involving guidance and counseling teachers, school counselors, and students selected through purposive sampling. Data were collected through in-depth interviews, observation, and document analysis, and analyzed using an interactive data analysis model consisting of data reduction, data display, and conclusion drawing. The research findings indicate that the integration of Islamic values ​​in guidance and counseling services is based on a holistic perspective of human development that integrates spiritual, moral, emotional, and psychological dimensions. In practice, Islamic values ​​are embedded in counseling goals, techniques, and counselor roles, so that counseling services can function as an instrument for prevention, development, and transformation of character education. Therefore, this suggests that integrating Islamic values ​​into guidance and counseling services provides a sustainable and effective strategy for strengthening character education in contemporary educational environments.